Edukasyong Pantahanan at Pangkabuhayan (EPP) Modular Distance Learning Amid Class Suspensions: Perspectives and Learning Outcomes - Nercuit, Michelle (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effectiveness of Edukasyong Pantahanan at Pangkabuhayan Modular Distance Learning (EPP-MDL) during class suspensions and its relationship to Grade V pupils’ competencies and academic performance in the Bohol Division for the school year 2025–2026. Anchored on Pragmatist Theory, Spiral Progression Theory, and Social Efficiency Theory, the study employed a descriptive-correlational research design using a modified and adapted questionnaire based on established module evaluation tools and MELC guidelines. Respondents included school heads, teachers, home learning facilitators, and learners selected through proportionate stratified sampling. Data were analyzed using weighted mean, percentage, and Pearson correlation. Findings revealed that EPP-MDL implementation was generally “moderately implemented” across delivery, instructional quality, monitoring, and policy management. Teachers were found to have adequate qualifications and training, while home learning facilitators primarily provided supervisory support. Resource availability was moderate, with both printed and digital modules utilized. Learners demonstrated competent skill levels, with stronger performance in home-based tasks and weaker outcomes in entrepreneurship and ICT areas. Academic performance showed gradual improvement across quarters, indicating sustained learning despite disruptions. Significant relationships were found between implementation, competencies, and grades, with competencies showing the strongest link to academic performance. The study concludes that modular learning supports continuity of education but requires improvements in instructional support, resource provision, and monitoring systems. It recommends strengthening capacity-building initiatives, enhancing parental involvement, and improving module design and distribution. This study aligns with SDG 4 (Quality Education) by promoting inclusive and continuous learning and supports SDG 8 (Decent Work and Economic Growth) through the development of practical livelihood skills. The findings contribute to educational and socio-economic sustainability by informing policy and improving instructional systems for resilient learning environments.